The Influence Of Profitability On Company Value With Company Size As A Moderating Variable - Wahyudi, Adi Aris; Choeriyah, Putri Utami (International Journal of Education, Information Technology, and Others, 2025)
This study aims to examine the effect of Return On Investment (ROI) on Firm Value with Company Size as a Moderating Variable. This study uses secondary data with the population of this study are 10 consumer goods industry companies listed on the Indonesia Stock Exchange in 2016-2019. The research sample used in this study was 11 companies selected based on Purposive Sampling Technique. The method used in this research is the multiple linear analysis method. The results showed that there was a significant influence between Return On Investment on Company Value with Company Size as a Moderating Variable.